The RNA-binding landscape of RBM10 and its role in alternative splicing regulation in models of mouse early development. Issue 1 (2nd January 2017) - Rodor, Julie; FitzPatrick, David R.; Eyras, Eduardo; Cáceres, Javier F.
ABSTRACT: Mutations in the RNA-binding protein, RBM10, result in a human syndromic form of cleft palate, termed TARP syndrome. A role for RBM10 in alternative splicing regulation has been previously demonstrated in human cell lines. To uncover the cellular functions of RBM10 in a cell line that is relevant to the phenotype observed in TARP syndrome, we used iCLIP to identify its endogenous RNA targets in a mouse embryonic mandibular cell line. We observed that RBM10 binds to pre-mRNAs with significant enrichment in intronic regions, in agreement with a role for this protein in pre-mRNA splicing. In addition to protein-coding transcripts, RBM10 also binds to a variety of cellular RNAs, including non-coding RNAs, such as spliceosomal small nuclear RNAs, U2 and U12. RNA-seq was used to investigate changes in gene expression and alternative splicing in RBM10 KO mouse mandibular cells and also in mouse ES cells. We uncovered a role for RBM10 in the regulation of alternative splicing of common transcripts in both cell lines but also identified cell-type specific events. Importantly, those pre-mRNAs that display changes in alternative splicing also contain RBM10 iCLIP tags, suggesting a direct role of RBM10 in these events. Finally, we show that depletion of RBM10 in mouse ES cells leads to proliferation defects and to gross alterations in their differentiation potential. These results demonstrate a role for RBM10 in the regulation of alternative splicing in two cell models of mouse early development and suggests that mutations in RBM10 could lead to splicing changes that affect normal palate development and cause human disease.